Genetic diversity of apple‐ and crabapple‐infecting isolates of Venturia inaequalis in Pennsylvania, the United States, determined by microsatellite markers. Issue 2 (3rd January 2018) - Sitther, V.; Garrido Haro, P. A.; Molineros, J. E.; Garzon, C. D.; Jiménez‐Gasco, M. M.
Summary: Apple scab caused by Venturia inaequalis is the most destructive disease of apple worldwide. In this study, genetic diversity of 101 V. inaequalis isolates from cultivated apples and ornamental crabapples in Pennsylvania (PA, USA) was characterized using 14 microsatellite markers. A total of 157 alleles ranging from 5 ( Vitg9/ 99) to 26 ( Vica10/154 ) per locus were detected. Regardless of the host of origin, isolates were grouped into five clusters, which were largely supported by STRUCTURE and principal coordinate analysis. Cluster analyses based on genetic distances and population structure analysis suggest very small differentiation (PhiPT ranging from 0.016 to 0.103, depending on the population comparison) between apple and crabapple isolates of V. inaequalis . Pairwise comparisons among populations from different locations showed very low differentiation, and POPGENE analysis indicated frequent migration of alleles ( Nm = 1.47). In pathogenicity tests using a detached leaf assay, isolates of V. inaequalis from crabapple caused characteristic scab symptoms on apple and were highly virulent. Results of the study indicate that scab lesions in crabapple trees in close vicinity to apple orchards could serve as reservoirs for spread of the pathogen. Movement of inoculum among locations and between hosts may be responsible for the limited population structure observed. Understanding the population structure of V. inaequalis isolates is significant for apple scab management as crabapples are often used as pollinizers and rootstock in apple orchards, and as ornamental trees.